Lymph node recurrence and re-excision after primary tumor resection of a histiocytic sarcoma of duodenal origin: a case report - Kohei Segami; Shinjiro Kobayashi; Masaki Hiwatari; Yuta Ogura; Masafumi Katayama; Satoshi Koizumi; Motohiro Chosokabe; Junki Koike; Takehito Otsubo (Surgical Case Reports, 2022)
Abstract Background Histiocytic sarcoma is a rare malignant tumor that is similar in characteristics to a mature histiocyte/macrophage and is a relatively new disease entity. In approximately one-third of cases, the site of origin is a lymph node; development from the gastrointestinal tract, spleen, soft tissue, and skin has further been reported. The tumor characteristics are not well-understood as reports on its clinical presentation and treatment are limited. We report a case of duodenal primary histiocytic sarcoma. Case presentation An elevated lesion in the second part of the duodenum was detected in a 70-year-old woman during routine examination using upper gastrointestinal tract endoscopy. Blood biochemistry findings were normal for tumor markers. No abnormal findings were observed in the blood count and biochemical examination. Upper gastrointestinal endoscopy revealed a 20-mm elevated lesion with a slight depression in the center, opposite to the papilla of the descending duodenum. The biopsy showed erosions of the mucosal epithelium and inflammatory cell infiltration, but no evidence of malignancy. Ultrasound-guided endoscopy revealed an ischemic tumor of submucosal origin, and bowel biopsy suggested a histiocytic sarcoma. Distant metastasis and lymph node enlargement were absent on abdominal sonography, computed tomography, and magnetic resonance imaging. Duodenal segmental resection was performed. Immunostaining of the excised lesion was positive for CD68, CD163, CD4, CD5, CD15, and CD45 and negative for CD1a, CD21, CD34, MPO, and S-100 protein. Ki-67 positivity was approximately 20%. Based on these findings, the diagnosis of histiocytic sarcoma was confirmed. Ten months after the surgery, a lymph node recurrence in the dorsum of the pancreatic uncus was observed. No evidence of recurrence was found in any other part; hence, we performed pancreaticoduodenectomy. Pathological findings of the excised lymph node confirmed the recurrence of histiocytic sarcoma in the lymph node. Conclusions This is the first reported case of a duodenal primary histiocytic sarcoma with recurrence in the lymph node after the primary resection. The patient was treated for recurrence by lymph node excision and pancreaticoduodenectomy.